A Customizable, Low-Cost Perfusion System for Sustaining Tissue Constructs. (December 2018) - O'Grady, Brian J.; Wang, Jason X.; Faley, Shannon L.; Balikov, Daniel A.; Lippmann, Ethan S.; Bellan, Leon M.
The fabrication of engineered vascularized tissues and organs requiring sustained, controlled perfusion has been facilitated by the development of several pump systems. Currently, researchers in the field of tissue engineering require the use of pump systems that are in general large, expensive, and generically designed. Overall, these pumps often fail to meet the unique demands of perfusing clinically useful tissue constructs. Here, we describe a pumping platform that overcomes these limitations and enables scalable perfusion of large, three-dimensional hydrogels. We demonstrate the ability to perfuse multiple separate channels inside hydrogel slabs using a preprogrammed schedule that dictates pumping speed and time. The use of this pump system to perfuse channels in large-scale engineered tissue scaffolds sustained cell viability over several weeks.